PENERAPAN METODE GROUP INVESTIGATION DALAM PEMBELAJARAN MENULIS PUISI PADA SISWA KELAS X - Dewi, Adinda Meifa (IKIP Siliwangi, 2020)
The problem in this research is the planner, the implementation and the results of the application of the method of group investigation in learning to write poetry in class X BDP 1 students at SMK Cendekia Batujajar. This research is based on the lack of students' skills in writing poetry. The aim of this research is to describe the application of the method of group investigation in the process of learning to write poetry in X BDP 1 students at SMK Cendekia Batujajar. This research method is a descriptive qualitative method. The research technique is observation and testing. The research subjects were student X BDP 1 with a total of 31 students. The results of the study are 1) planning the application of the group investigation method in learning is appropriate, 2) the implementation of the group investigation method when learning is in accordance with the prepared lesson plans, 3) the results of the application of the group investigation method are shown with an average initial test score of 76 and test scores end of 85 there was an increase. In conclusion, the group investigation method is effectively applied in poetry writing skills.Keywords: Learning Outcomes, Group Investigation, Writing Poetry